2015
DOI: 10.1063/1.4927094
|View full text |Cite
|
Sign up to set email alerts
|

Flowing-afterglow study of electron-ion recombination of para–H3+ and ortho–H3+ ions at temperatures from 60 K to 300 K

Abstract: Detailed measurements employing a combination of a cryogenic flowing afterglow with Langmuir probe (Cryo-FALP II) and a stationary afterglow with near-infrared absorption spectroscopy (SA-CRDS) show that binary electron recombination of para-H3(+) and ortho-H3(+) ions occurs with significantly different rate coefficients, (p)αbin and (o)αbin, especially at very low temperatures. The measurements cover temperatures from 60 K to 300 K. At the lowest temperature of 60 K, recombination of para-H3(+) is at least th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…In our previous studies we monitored the approach to equilibrium of afterglow plasmas in He/Ar, He/Ar/H 2 and He/Ar/D 2 gas mixtures. 35,40,41 The kinetic temperature of ions (T kin-ion ) was obtained from Doppler broadening of measured absorption lines. The rotational temperature of ions (T rot ) was determined by measuring relative populations of the lowest rotational states.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies we monitored the approach to equilibrium of afterglow plasmas in He/Ar, He/Ar/H 2 and He/Ar/D 2 gas mixtures. 35,40,41 The kinetic temperature of ions (T kin-ion ) was obtained from Doppler broadening of measured absorption lines. The rotational temperature of ions (T rot ) was determined by measuring relative populations of the lowest rotational states.…”
Section: Methodsmentioning
confidence: 99%
“…The rotational temperature of ions (T rot ) was determined by measuring relative populations of the lowest rotational states. 41 The electron temperature (T e ) was estimated by monitoring the losses due to the ambipolar diffusion. 29,41,42 Because excited particles can heat the electrons in superelastic collisions, we also monitored the presence of the ground and the first vibrational state of the a 3 S + u electronic state of (He 2 )* and the 3s 2 3p 5 ( 2 P 0 1/2 )3d 2 [3/2] 0 state of (Ar)* during the afterglow.…”
Section: Methodsmentioning
confidence: 99%
“…Para-H 3 + DR rates increase, while ortho-H 3 + rates decrease. As such, the dissociative recombination patterns were experimentally determined below 100 K. Later, in 2015, it would be found that the 60 K binary recombination rate for para-H 3 + (1.8 × 10 –7 cm 3 s –1 ) is at least three times larger than for ortho-H 3 + (0 +5 × 10 –8 cm 3 s –1 ) …”
Section: H3 Rydberg Moleculesmentioning
confidence: 87%
“…As such, the dissociative recombination patterns were experimentally determined below 100 K. Later, in 2015, it would be found that the 60 K binary recombination rate for para-H 3 + (1.8 × 10 −7 cm 3 s −1 ) is at least three times larger than for ortho-H 3 + (0 +5 × 10 −8 cm 3 s −1 ). 43 In 2013, studies extended conditions down to 50 K for the first time for both H 3 + and D 3 + DR. Differing from neutral ternary recombination (He assisted), electron-assisted ternary recombination (electron-collisional radiative recombination or E-CRR) may also substantially contribute to effective recombination rates, which was suggested by theory and observed in an Ar + dominated plasma.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In normal H 2 , the para/ortho ratio is 1/3, corresponding to the thermal equilibrium at 300 K (for discussion, see Zymak et al 2013;Hejduk et al 2012). As the rotational excitation in hydrogen gas is thermalized only within para and ortho manifolds, H 2 gas flowing through the gas inlet system into the trap volume is not thermalized at trap temperatures below 200 K (Zymak et al 2013;Hejduk et al 2015). The gas number density inside the ion trap is determined using a spinning rotor gauge and a calibrated ionization gauge with estimated uncertainty of 20%.…”
Section: Experiments and Data Analysismentioning
confidence: 99%